Platelet Proteasome Activity and Metabolism Is Upregulated during Bacterial Sepsis - Grundler Groterhorst, Katharina (Int J Mol Sci, 2019)
Dysregulation of platelet function can contribute to the disease progression in sepsis. The proteasome represents a critical and vital element of cellular protein metabolism in platelets and its proteolytic activity has been associated with platelet function. However, the role of the platelet proteasome as well as its response to infection under conditions of sepsis have not been studied so far. We measured platelet proteasome activity by fluorescent substrates, degradation of poly-ubiquitinated proteins and cleavage of the proteasome substrate Talin-1 in the presence of living E. coli strains and in platelets isolated from sepsis patients. Upregulation of the proteasome activator PA28 (PSME1) was assessed by quantitative real-time PCR in platelets from sepsis patients. We show that co-incubation of platelets with living E. coli (UTI89) results in increased degradation of poly-ubiquitinated proteins and cleavage of Talin-1 by the proteasome. Proteasome activity and cleavage of Talin-1 was significantly increased in α-hemolysin (HlyA)-positive E. coli strains. Supporting these findings, proteasome activity was also increased in platelets of patients with sepsis. Finally, the proteasome activator PA28 (PSME1) was upregulated in this group of patients. In this study we demonstrate for the first time that the proteasome in platelets is activated in the septic milieu.